Strategic bootstrapping - Rutherford, Matthew W. (Babson College entrepreneurship research conference collection., 2015)
This book is about helping entrepreneurs sift through the "noise" regarding bootstrapping a start-up. Ultimately, the cold-hard facts on bootstrapping will be presented. Practically speaking, most entrepreneurs should avoid bootstrapping. However, realistically, most entrepreneurs will need to engage in some form of bootstrapping. The argument then, importantly, shifts to how should one bootstrap? In this era of lean start-ups, effectuation, and bricolage, bootstrapping is oft romanticized but seldom analyzed. This book is different from other bootstrapping books in two key ways. First, it draws on evidence from scientific study to offer best practices. Second, it utilizes this evidence to help entrepreneurs thrive-- not just survive